DESAIN GAMBAR BRAILLE SEBAGAI UPAYA MENGENALKAN OBJEK BINATANG SECARA VISUAL PADA ANAK PENDERITA TUNANETRA - Tyas, Dwi Estining; Safitri, Megawati Andi; Prabandari, Titis Febri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The human with special needs are living creatures that were created with limitations. One of them is limited in seeing or blind. So far, most blind children just introduced braille letters so that they are less able to recognize the image as a whole. For example, the shape and characteristics of the animals that have body fat, short, tall, and so forth. Blind children only hear the shape and characteristics of the non-blind.Visual object selected animals because each animal has a shape and a very different characteristics. For example, elephants have different characteristics with tigers. Elephants have a distinctive character that is big ears, big body, long proboscis. While the character has a tiger striped body and sharp teeth.Braille image recognition, enabling blind children are able to recognize a visual object animal quickly. Because it needs to be made an additional guidelines in addition to Braille. In this wide image that does not mean leaving the characteristics of the range, but more emphasis on how to become a point of visualized braille pictures of animals.